Tunisians demand accountability for dual citizen who served in Israeli army during Gaza war (Middle East Monitor, 2025)
Dozens of Tunisians have demanded accountability for a Tunisian-Israeli citizen who served in the Israeli occupation army during the war on the besieged Gaza Strip. Photos and videoclips of a Tunis…
Keywords: Guerre de Gaza (2023-....); Judaïsme – Djerba

Polémique en Tunisie : Un chanteur d’origine juive apparu en uniforme de l’armée israélienne (2025)
Le chanteur tunisien d’origine juive, identifié comme Sahi Maimoun, est au centre d’une vive controverse après la diffusion d’images le
Keywords: Guerre de Gaza (2023-....); Judaïsme – Djerba